The Application of Field Trip Learning Method to Mangrove Forest as a Source of Geography Learning - Asyari, Wahid Hasyim; Munandar, Aris; Samadi, Samadi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
In this study, the aim was to determine differences in the results of student scores using the field trip learning method, both pre-test and post-test on the field trip learning method. This study uses a quantitative research approach with a type of experimental research. This type of research is an experiment that uses the population in this study is class XI IPS SMAN 1 Sindang ranging from XI IPS 1 to XI IPS 4, which consists of 144 students, but the sample in this study is class XI IPS 1 and XI IPS 2 consisting of 36 students per class when totaled into 72 student samples. The sampling technique carried out in this study is using purposive sampling techniques. The method of data collection in this study is through test exam results conducted pre-test and post-test in learning to see the difference in student scores by providing test, while the data analysis technique used is the T-test analysis with the aim of seeing the difference in value results before and after being given online and offline field trip learning treatment. The data analysis technique used is the T-test analysis with the aim of seeing the difference in value results before and after being given online and offline field trip learning treatment. The results of this study were that there were differences in the learning outcomes of the control class and the experimental class both in the pre-test and post-test. The control class in the pre-test had an average score of 67.33, and after being given offline field trip treatment, the average value increased to 79.89, while the experimental class in the pre-test had an average value of 65.61 and after being given an online field trip treatment the average value increased to 80.38. It can be concluded that these two field trip learning methods can improve student scores, although, in this learning method, there are advantages and disadvantages of each.